Design thinking for practice-based intervention: Co-producing the change points toolkit to unlock (un)sustainable practices. (March 2020) - Hoolohan, Claire; Browne, Alison L.
Abstract : This paper develops connections between design thinking and social practice theories, presenting a toolkit intended to support the development of sustainability interventions and policies capable of encouraging sustainable practices. Key developments in design thinking and social practice theories are critically examined, and a toolkit is presented that sensitively combines their conceptual and methodological insights. The toolkit is one of the first resources that enables practitioners to operationalise social practice theories without substantial prior engagement or training. It thereby offers an accessible resource to support the design of initiatives that could disrupt resource intensive practices and support the emergence and normalisation of less resource intensive alternatives. This paper specifically addresses the contribution the toolkit makes to advancing discussions regarding practice-oriented design. Highlights: Connections between social practice theories and design thinking are developed. Social Practice Theories extend focus towards a socio-technical system focus. Design Thinking provides immersive participatory methods for intervention planning. We present a toolkit to aid creation of practice-based sustainability interventions. A co-productive approach is outlined to enable others to develop practicable outputs.